The effect of zirconium on the Ti-(42-46 at.%)Al system. (December 2022) - Musi, Michael; Kardos, Stefan; Hatzenbichler, Lukas; Holec, David; Stark, Andreas; Allen, Melissa; Güther, Volker; Clemens, Helmut; Spoerk-Erdely, Petra
Abstract: In recent years, Zr has emerged as a promising alloying element for intermetallic γ-TiAl based alloys to improve their mechanical properties. The present work focuses on the influence of this element on the microstructure and the thermodynamic phase equilibria in the ternary Ti-(42-46)Al-(2-4)Zr (at.%) system. Alloying with Zr was found to increase the amount of the γ phase in the microstructure of cast material densified by hot-isostatic pressing. Simultaneously, the material's hardness increased due to solid solution strengthening as well as the refinement of lamellae in the α2 /γ colonies. With respect to the phase transformation behaviour, a significant decrease of the solidus temperature was observed in the high Zr alloyed material variants. In combination with the stabilization of the γ phase, this essentially results in a narrowing of the single α phase field region in the Ti-Al-Zr phase diagram derived in this work. In situ high-energy X-ray diffraction was performed on Ti-46Al-2Zr and Ti-46Al-4Zr (at.%) specimens to investigate the phase transitions above and below the solidus temperature by utilizing two different experimental setups. These experiments showed that upon heating, small amounts of β phase are formed in both alloys prior to the transition into the peritectic α+β+L phase field region. Furthermore, an additional heat treatment study was conducted to determine the influence of Zr and temperature on the resulting microstructure. The combination of X-ray diffraction techniques with ab-initio calculations revealed a significant asymmetric influence of Zr on the lattice parameter of the γ phase, resulting in a decreasing c/a ratio. Graphical abstract: Image, graphical abstract